Empowering financial education by banks: Social media as a modern channel - Iwa Kuchciak; Justyna Wiktorowicz (Journal of Risk and Financial Management, 2021)
Financial literacy is extremely important, both from the perspective of the financial well-being of individuals and the stability of the financial market and the whole economy. The more financially literate a bank's customers are, the more frequently and consciously they use financial products and services. Thus, banks are potentially significant stakeholders in the financial education process. Considering that social media have become the leading channel for communication and relationship building, especially regarding young clients, this channel should also be used by banks to increase financial literacy. The aim of this paper is to assess banks' involvement in financial education activities through social media. We assume that banks use social media as a modern and attractive channel for improving financial education among social media users. The empirical analysis was conducted using several data sources, including non-financial statements and a unique self-collected dataset that describes the specifics of the most popular social media platforms (like Facebook, Twitter, YouTube, Instagram, GoldenLine, and LinkedIn) in the activities of commercial and cooperative banks in Poland between 2010 and 2019. Descriptive statistical methods and cluster analysis were used. The results show that educational activities provided by banks in Poland differ for each social media channel. Additionally, although financial education topics have become more popular among content published by banks, there is a huge disproportion between cooperative and commercial banks. Generally, banks that are more active on social media (mostly commercial banks) also pay more attention to the financial education context.
Keywords: 330; financial literacy; banking sector; social media